2001
DOI: 10.1091/mbc.12.4.1147
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Acyl-Coenzyme A-Binding Protein Affects Sphingolipid Synthesis and Causes Vesicle Accumulation and Membrane Defects inSaccharomyces cerevisiae

Abstract: Deletion of the yeast gene ACB1 encoding Acb1p, the yeast homologue of the acyl-CoA-binding protein (ACBP), resulted in a slower growing phenotype that adapted into a faster growing phenotype with a frequency Ͼ1:10 5 . A conditional knockout strain (Y700pGAL1-ACB1) with the ACB1 gene under control of the GAL1 promoter exhibited an altered acyl-CoA profile with a threefold increase in the relative content of C18:0-CoA, without affecting total acyl-CoA level as previously reported for an adapted acb1⌬ strain. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
118
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 50 publications
17
118
0
Order By: Relevance
“…7) is not surprising and was observed previously in both Saccharomyces cerevisiae and animal systems (Mandrup et al, 1993;Knudsen et al, 1994;Gaigg et al, 2001;Huang et al, 2005;Oikari et al, 2008). Indeed, the increase in the contribution of saturated acyl-CoAs to the total acyl-CoA pool observed in this study is similar to results reported in yeast and mice overexpressing ACBP (Mandrup et al, 1993;Huang et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…7) is not surprising and was observed previously in both Saccharomyces cerevisiae and animal systems (Mandrup et al, 1993;Knudsen et al, 1994;Gaigg et al, 2001;Huang et al, 2005;Oikari et al, 2008). Indeed, the increase in the contribution of saturated acyl-CoAs to the total acyl-CoA pool observed in this study is similar to results reported in yeast and mice overexpressing ACBP (Mandrup et al, 1993;Huang et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Here, we found that replication of WT BMV RNA3 was inhibited 25-fold (Fig. 3) by deleting ACB1, encoding an acyl-CoA-binding factor involved in membrane sphingolipid biosynthesis (43). This finding underscores the importance of membrane properties to BMV RNA replication and implies that multiple classes of membrane lipids are required for a functional RNA replication complex.…”
Section: Discussionmentioning
confidence: 54%
“…Targeted disruption of the yeast ACBP gene (ACB1) revealed that ACBP deficiency results in increased levels of C18:0 acyl-CoA esters and a decrease in the amount of total C26:0 fatty acids, indicating that transport of FA toward elongation is impaired by lack of ACBP. Furthermore, sphingolipid and ceramide amounts were reduced, membrane structure was altered, and vesicular transport was compromised (23)(24)(25).…”
mentioning
confidence: 99%